An experimental investigation on tapered wings with leading-edge protuberances - Ee, Marcus Joon Leng (Nanyang Technological University, 2023)
Particle Image Velocimetry (PIV) experiments were conducted in a water tunnel to study vortex interactions around tapered swept wings with leading edge tubercles. Two airfoil models based on the SD7032 airfoil profile were tested at Reynolds number 9100 and angles of attack (α) of -10°,10° and 25°, with the latter two representing the pre-stall and post-stall regimes respectively. Flow visualisation was also performed on airfoils at negative angles of attack for the first time. Results at positive angles of attack show that the baseline wing experiences significant flow separation at the outboard region while flow remains attached at the inboard region. Leading edge tubercles are shown to provide effective flow control by maintaining flow attachment and mitigating shear layer formation at high angles of attack even at the outboard region of the wing. At higher pitch angles, flow also reattaches along the tubercle peaks while most of flow along the baseline wing remains separated. Flow visualisation at negative angle of attack shows high vorticity along the pressure surface of both wings. Vorticity of the tubercled wing was noticeably worse than that of the baseline wing, suggesting a negative effect of tubercle curvature on flow stability at negative angles of attack.